Mycelium-bound lipase from Penicillium citrinum as biocatalyst for the hydrolysis of vegetable oils - Lima, Rafaela T.; Alves, Alex M.; de Paula, Ariela V. [UNESP]; de Castro, Heizir F.; Andrade, Grazielle S.S. (Elsevier, 2019)
Mycelium-bound lipase from filamentous fungus has been extensively studied as an alternative biocatalyst used in biotransformation processes. In this work, Penicillium citrinum URM 4216 was assessed as a potential producer of mycelium-bound lipase and its catalytic activity was investigated to yield concentrated polyunsaturated fatty acids from vegetable oils. Under the established growth conditions and using olive oil as an inducer, P. citrinum was able to produce lipase having high mycelium-bound activity (271.67 ± 10.47 U g−1) revealing suitable biochemical (optimum pH = 8.0 at 45 °C) and kinetic (Km = 136.51 μmol L−1min−1, Vmax = 267.33 μmol g−1min−1) properties and thermal stability (half-life time of 1.8 h at 60 °C) to mediate biotransformation reactions. By applying factorial design, the hydrolysis of soybean oil yielded 38% at 38 °C using oil/buffer ratio of 20% in the presence of 2.5% of an emulsifying agent for 3 h. The hydrolysis degree was increased to 96% by replacing the conventional heating system for ultrasonic irradiation and increasing the incubation time to 9 h. Similar degrees of hydrolysis (>84%) were achieved using other rich polyunsaturated vegetable oils (sunflower, olive and canola oils); confirming the specificity of this mycelium-bound lipase for polyunsaturated fatty acids, such as oleic and linoleic acids.
Keywords: Hydrolysis; Mycelium-bound lipase; Penicillium citrinum; Ultrasonic irradiation; Vegetable oils; Whole-cells